Influence of soil amendments on the growth and yield of rice in acidic soil - Abdul Halim, Nur Sa’adah; Abdullah, Rosazlin; Karsani, Saiful Anuar; Osman, Normaniza; Panhwar, Qurban Ali; Ishak, Che Fauziah (M D P I AG, 2018)
In Malaysia, about 0.5 million ha of acid sulfate soils are found scattered over the east, west,and Sabah and Sarawak regions that can potentially be cultivated with paddy. This type of soil is acidic and not immediately suitable for crop production unless improved by applying some amendments. Thus, the current study was carried out to investigate the effects of various types of soil amendments on the growth, yield, and physiological responses of rice grown in xtremely acidic conditions using ground magnesium limestone (GML), basalt, biochar, and compost as soil amendments. The acid sulfate soil with a pH of 3.76 was obtained from a paddy field in Merbok, Kedah. The plant responses were evaluated based on agronomic, physiological, and yield performance. The compost-treated rice showed the best performance in all three criteria. Compost treatment increased the soil pH up to 6.25.Physiological performances such as chlorophyll, photosynthetic rate, and water use efficiency were higher after compost treatment, while transpiration and stomatal conductance showed the highest after GML treatment. It can be concluded that the addition of compost as a soil amendment can increase soil pH and create favorable soil conditions for rice cultivation in acid sulfate soil, leading to improved rice growth performance.